2021
DOI: 10.4041/kjod.2021.51.4.260
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cone-beam computed tomography evaluation of hard and soft tissue thicknesses in the midpalatal suture region to facilitate orthodontic mini-implant placement

Abstract: Objective To identify the most favorable sites that optimize the initial stability and survival rate of orthodontic mini-implants, this study measured hard and soft tissue thicknesses in the median and paramedian regions of the palate using cone-beam computed tomography (CBCT) and determined possible sex- and age-related differences in these thicknesses. Methods The study sample comprised CBCT images of 189 healthy subjects. The sample was divided into four groups accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The findings of the present study showed no evidence of differences in the dimensions of the upper jaw for the insertion of rapidly expanding mini-implants between the age groups studied; however, the dimensions decreased from the first premolar to the second molar in a similar way to that reported by Oh et al, 20 while those of soft tissue were more homogeneous, agreeing with Yadav et al 21 Although the age groups studied were constructed based on what was reported by previous studies,…”
Section: Discussionsupporting
confidence: 88%
“…The findings of the present study showed no evidence of differences in the dimensions of the upper jaw for the insertion of rapidly expanding mini-implants between the age groups studied; however, the dimensions decreased from the first premolar to the second molar in a similar way to that reported by Oh et al, 20 while those of soft tissue were more homogeneous, agreeing with Yadav et al 21 Although the age groups studied were constructed based on what was reported by previous studies,…”
Section: Discussionsupporting
confidence: 88%
“…One critical factor that influences miniscrew placement in this region is the thickness of the soft tissue. 29 The palatal slope is covered by thick palatal mucosa, and to ensure that the miniscrews do not become buried under the mucosa, it can be beneficial to use miniscrews with longer necks and apply an acrylic pad without delay. Determining the appropriate length of miniscrews and their insertion depth to prevent perforation into the maxillary sinus region can be aided by CT evaluations, which offer insights into the thickness of both bone and soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In order to gain space for the missing tooth, the maxillary left molars were distalized with a MCPP. The midpalatal and anteroparamedian regions have been favored as TSAD recipient sites since they are known for their sufficient bone thickness and density to support the skeletal anchors 12,13 . Also, they allowed for easy access, little anatomical interference, and high stability of miniscrew anchors with a failure rate of less than 5% 14 .…”
Section: Discussionmentioning
confidence: 99%